Esensi Ekstrakurikuler Angklung Di SD Darul Hikam 2 Sebagai Upaya Mempertahankan Eksistensi Budaya Indonesia Di Tengah Arus Globalisasi - Annisa Azzahra Julianty; Desi Nursyifa Ramdhani; Jannah Mutiarani Pradana; Agus Mulyana (Pendekar : Jurnal Pendidikan Berkarakter, 2023)
The aim of this research is to be able to find out extracurriculars in several schools, both private and state, and analyze the advantages, disadvantages, strengths and weaknesses of these schools' extracurriculars. The method used in this research is descriptive qualitative method. The research we conducted was field research where school principals and extracurricular coaches were the subjects. Data collection was taken by means of observation, interviews and documentation. After conducting the research, the results showed that there were fewer people interested in the angklung extracurricular activities at Darul Hikam 2 Elementary School compared to other extracurricular activities, so we as researchers are trying to maintain the existence of Indonesian culture in the midst of globalization by involving playing this angklung musical instrument in the learning process using the playing while learning method. , the aim of which is to know and learn traditional regional musical instruments and foster a sense of love for regional culture.